Da multa no cumprimento de sentença para o pagamento de quantia certa - Monteiro, Vitor José de Mello (2009)
The study s main purpose is to analyze the fine included in the Brazilian rules by the law nº 11.232/05 which, in a reasonable period of time, became an object of great controversy in the course of doctrinal and jurisprudential plans and regarding some attainments aspects. The point, therefore, was to sketch one methodology analysis of this new modality of form sanction in order to insert it in the Brazilian s context of procedural law without attacking, however, the jurists principles and guarantees, especially the ones of constitutional level. In addition, the necessity to extract of the institute s maximum possible effectiveness was not forgotten. In consequence, were studied since the most basic requirements so that duty application could have been cogitated until its more specific elements. Of this systemize study, conclusions had emerged on the incidence or not of the related penalty to the situations, until then, little explored by the doctrine and of rare verification in the national courts. It mentioned, also, amongst other peculiar characteristics of this fine, the purpose to confer more authority to the sentences that condemn to the payment of certain amount, in the measure where the debtor will count on a stated period of fifteen days to effect the spontaneous obligation s fulfillment, duly warned about the related penalty s incidence